Anti‐inflammatory effect of lanoconazole on 12‐O‐tetradecanoylphorbol‐13‐acetate‐ and 2, 4, 6‐trinitrophenyl chloride–induced skin inflammation in mice. Issue 2 (27th November 2019) - Nakamura, Aki; Uratsuji, Hideya; Yamada, Yoshihito; Hashimoto, Kei; Nozawa, Naoki; Matsumoto, Tatsumi
Summary: Background: Lanoconazole (LCZ) is a topical antifungal agent clinically used to treat fungal infections such as tinea pedis. LCZ has not only antifungal effects but also anti‐inflammatory effects, which have the potential to provide additional clinical benefits. However, the characteristic features of the inhibitory effects of LCZ on skin inflammation remain unclear. Objective: We evaluated the inhibitory effects of topical application of LCZ, and compared the effects of LCZ with those of other antifungal agents including liranaftate, terbinafine and amorolfine. Methods: Each antifungal agent was topically applied on 12‐ O ‐tetradecanoylphorbol‐13‐acetate‐induced irritant dermatitis and 2, 4, 6‐trinitrophenyl chloride‐induced contact dermatitis in mice (BALB/c). The ear thickness, myeloperoxidase activity and inflammatory mediator contents were evaluated. Results: LCZ dose‐dependently suppressed 12‐ O ‐tetradecanoylphorbol‐13‐acetate‐induced irritant dermatitis, suppressed the production of neutrophil chemotactic factors such as keratinocyte‐derived chemokine and macrophage inflammatory protein‐2, and inhibited neutrophil infiltration to the inflammation site. Moreover, 1% LCZ reduced the ear swelling in mice with 2, 4, 6‐trinitrophenyl chloride‐induced contact dermatitis in accordance with the inhibition of interferon‐γ production. The inhibitory potency of LCZ on these types of dermatitis in mice was stronger than that of other types of antifungal agents. Conclusion: The anti‐inflammatory effects of LCZ were exerted through the inhibition of inflammatory mediator production. These effects may contribute to the relief of dermatitis symptoms in patients with tinea pedis.